Antiactivator (Antikinase) Activity of Human Plasma and Its Blocking by Parachloromercuribenzoate and Salicylate - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1971)
A two-stage assay for fibrinolytic antiactivator (FAA), independent of the concentration of antifibrinolysin (AFL) in plasma, is based upon the essentially complete precipitation of profibrinolysin (PFL) in euglobulin precipitated at pH 5.6. In the first stage a standardized amount of urokinase converts part or all of the PFL to fibrinolysin (FL) depending upon the concentration of FAA in the test plasma. FL and AFL remain in the supernatant solution during precipitation of the euglobulins. In stage two PFL from the euglobulin precipitate is completely activated by urokinase and the generated fibrinolytic activity is estimated from turbidity measurements of the fibrinogen remaining after a standardized incubation period.FAA is strongly blocked by parachloromercuribenzoate and more weakly blocked by salicylate. The dissociation constant of the UK-FAA complex is estimated to be 2 × 10∼9M. The FAA in plasma can block 5600 CTA units UK/ml plasma (1.1 x 10∼6M). For UK concentrations much lower than 9.5 U/ml (2 × 10-9 M), it was calculated that 590 u UK are bound per ml for every unit free UK/ml. At 37 ° C the kinetic constant of PFL activation by UK is 1.25 × 105 sec-1 M-1.